1001 chess endgame exercises for beginners : the tactics workbook that also improves your endgame skills - Willemze, Thomas (New in Chess, 2022)
"The best place to start your tactics training is in the endgame! Chess is 99% tactics - and if you want to win more games, nothing works better than training tactics. Win a piece or find a mate. That will get you results. Since most of the pieces have left the board, endgame tactics have the clarity that enables you to grasp all basics concepts quickly and comprehensively. In the endgame, you can focus on what is important without any distractions by a couple of random pawns and pieces. In 1001 Chess Endgame Exercises for Beginners, IM Thomas Willemze does two things at once. He explains all the basic concepts, and provides you with a huge amount of exercises for each theme and each chess piece. Willemze uses all his experience as a coach, and his familiarity with the famous Step Method, to carefully build up your chess knowledge step-by-step. He shows you the strength of all pieces, from the lonely pawn to the almighty queen. And he guides you from the basics to more complex tactics in a highly instructive puzzle rush." --Back cover.